Dry sliding wear performance of Semi-Solid Al/LM6 cast Composite: Effect of silicon particles on worn surfaces. (2022) - Agarwal, Deepak; Dixit, Manish; kumar Dixit, Nitesh; Agarwal, Mayank
Abstract: Abrasive behavior for the wear properties according to the effect of silicon particles has been investigated for powder chip reinforced LM6 Aluminium alloy fabricated via. Semi-solid casting. Initially, a novel reinforcement was fabricated with the help of a ball milling process for 13% addition of silicon particulates inside the LM6 aluminium alloy powder and chip. In this process, fine aluminium powder (81microns) and chips of LM6 alloy (less than 60 μm) have been refined due to the impact of hard balls via the ball milling process. After the fabrication of reinforcement particulates, semi-solid casting was used to fabricate Si-rich semi-solid cast composite. Dry sliding wear for the fabricated composite has been conducted against the EN-31 steel plate hardened to 62HRC. Microstructure, EDX, and XRD have been analyzed to form the tribo-layer due to added Si particulates.